Sensitivitas dan spesifisitas lingkar pergelangan tangan sebagai prediktor obesitas dan resistensi insulin pada remaja akhir - Fitriyanti, Addina Rizky; Tjahjono, Kusmiyati; Sulchan, Mohammad; Sunarto, Sunarto (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2019)
Background: Obesity is one of the risk factors for insulin resistance. Insulin resistance plays an important role in the pathogenesis of cardiovascular disease. Wrist circumference has the potential for predicting obesity and insulin resistance.Objectives:. To evaluate the sensitivity and specificity of wrist circumference against obesity and insulin resistance in late adolescents.Methods: The design of this study is a crossectional study with a sample of 85 students at Diponegoro University Semarang. Data collected consisted of anthropometric measurements (body weight, height, wrist circumference, neck circumference, waist circumference and pelvic girth) and blood vein sampling (fasting blood glucose and fasting insulin). Statistical analyses used in this study were Pearson or R Spearman correlation test.Results: Wrist circumference was positively correlated with all biochemical parameters and anthropometric measurements except the waist hip ratio. Wrist circumference correlates positively and significantly with fasting insulin and HOMA-IR in male adolescents. The results of the ROC curve analysis showed that the AUC value of wrist circumference in male adolescents had better performance in predicting obesity (88% (95% CI, 76% - 100%)) than insulin resistance (81% (95% CI, 51% -100%)).Conclusion: Wrist circumference is one of the anthropometric measurements that can be used for predicting obesity and insulin resistance in late adolescents.